An Economic Analysis of Coastal Beach Safety Information-Seeking Behavior. (13th July 2017) - Kaminski, Abigail; Bell, Kathleen P.; Noblet, Caroline L.; Evans, Keith S.
Abstract : We estimate a bivariate probit model using data from a survey of Maine and New Hampshire beachgoers to (i) assess the impact of exposure to and contact with beach waters on safety information-seeking behaviors, and (ii) compare information-seeking behaviors for surf conditions and water quality information. We find that individuals who engage in certain high-contact recreation activities (i.e., swimming, fishing, surfing) are more likely to seek out safety information and that some potential drivers of this behavior affect searches differently for surf conditions versus water quality information.